Decision Paying Zakah Based on Religiosity and Income: Mediating Role of Awareness - Faruq, Muhammad Al; Yuliana, Indah; Ekowati, Vivin Maharani (Jurnal Aplikasi Manajemen, 2024)
Zakah is one of the pillars of Islam that must be fulfilled by a Muslim, which is helpful in purifying wealth and improving other Muslim’s standard of living to realize the people’s welfare. This study aimed to test the influence of religiosity and income on the decision to pay Zakah, mediated by awareness. The research method used is a quantitative research type with an explanatory approach to prove the truth of the research hypothesis. The study population was all muzakki from the professional Zakah category at BAZNAS Sidoarjo. The data collection technique used a questionnaire distributed to 225 respondents who had paid Zakah and was analyzed using Partial Least Squares (PLS). The results showed that religiosity did not directly affect the decision to pay Zakah. Income and awareness directly affect the decision to pay Zakah. Religiosity and income directly affect the awareness of paying Zakah. Awareness does not directly affect the decision to pay Zakah. Furthermore, awareness can mediate the influence of religiosity on the decision to pay Zakah, and awareness can mediate the influence of income on the decision to pay Zakah. The results of this study can be applied to improve the decision to pay Zakah by building the religiosity and income of muzakki through optimizing awareness so that the program from BAZNAS Sidoarjo in the future can be directed to optimizing the awareness of muzakki by providing socialization and assistance so that the decision to pay Zakah can increase and improve the welfare of the people in Sidoarjo Regency. Based on the study’s results, it is expected that BAZNAS Sidoarjo will carry out online reporting and accountability. PEMKAB Sidoarjo will socialise with OPD, BUMD, Village Government, and the Public. Then, Muzakki/ASN/Public increase literacy related to knowledge, experience/practice, and appreciation of Islam. Further researchers should include other variables and expand the discussion topics related to decisions to give infaq, sadaqah, and waqf.